Pedagogical Models in Physical Education and Their Influence on Psychological Outcomes and Character Development: A Bibliometric–Systematic Literature Review (2000–2026) - Nadila Maesara; Tite Juliantine; Yusuf Hidayat; Sucipto; Carsiwan; Bambang Abduljabar (Lembaga Bale Literasi, 2026)
Background: Pedagogical models such as Sport Education (SE), Teaching Personal and Social Responsibility (TPSR), Cooperative Learning (CL), Models-Based Practice (MBP) and Teaching Games for Understanding (TGfU) have come to the fore in physical education (PE) as vehicles for psychological and character development. Yet no integrative review has combined bibliometric mapping with systematic synthesis on the link between models and outcomes. Purpose: This Bibliometric–Systematic Literature Review (B-SLR) explored the volume, intellectual core, thematic evolution, and empirical evidence relating pedagogical models in PE to psychological and character outcomes from 2000 to 2026. Methods: Following the ten-step B-SLR framework of Marzi et al.,(2025) and PRISMA 2020, 1,323 Scopus-indexed records were retrieved; 154 formed the analytical subset, and 15 high-impact studies (PE001–PE015) underwent thematic synthesis following Thomas & Harden,(2008). Analyses used R v4.6.0 (bibliometrix, VOSviewer); quality was evaluated with MMAT 2018. Results: Annual production grew exponentially, with an inflection point in 2020 (n = 101) and a historical peak in 2025 (n = 227). Three productive hubs were identified: TPSR-USA (Wright), TPSR-Spain (Valero-Valenzuela, Manzano-Sánchez), and Sport Education-Portugal (Mesquita, Hastie). The model × outcome matrix indicated TPSR × Responsibility as the most researched pairing (n = 86) followed by SE × Engagement/Enjoyment (n = 30). The most prevalent explicit lens was Self-Determination Theory (48%), but 70% of studies operated without an explicit framework. Hybrid SE+TPSR models become a rising paradigm. 15 anchor studies (mean MMAT 11.8/14) were analyzed and four analytical themes emerged: motivational mechanisms; life-skills and responsibility learning through classroom structure; mastery climate and teacher-student relationships; and transfer-effect challenges. Conclusion Pedagogical models function as evidence-based vehicles for psychological and character development only when implemented with explicit transfer scaffolding within a need-satisfying motivational climate.